Chondrichthyan diversity, conservation status, and management challenges in Costa Rica - Espinoza, Mario; Díaz, Eric; Angulo, Arturo [UNESP]; Hernández, Sebastián; Clarke, Tayler M. (Frontiers, 2018)
Understanding key aspects of the biology and ecology of chondrichthyan fishes (sharks, rays, and chimeras), as well as the range of threats affecting their populations is crucial given the rapid rate at which some species are declining. In the Eastern Tropical Pacific (ETP), the lack of knowledge, unreliable (or non-existent) landing statistics, and limited enforcement of existing fisheries regulations has hindered management and conservation efforts for chondrichthyan species. This review evaluated our current understanding of Costa Rican chondrichthyans and their conservation status. Specifically, we (1) provide an updated checklist on the species richness, habitat use, and distribution patterns, (2) summarize the most relevant chondrichthyan studies (scientific publications, theses, and official technical reports), (3) identify knowledge gaps, (4) discuss fisheries-related threats, and (5) highlight the management challenges and research needs to effectively protect their populations. A total of 99 chondrichthyan species are formally recorded in Costa Rican waters, from which 15% are threatened with extinction and 41% are Data Deficient based on the IUCN (International Union for Conservation of Nature) Red List. A total of 121 studies were published between 1891 and 2017; 82% in the Pacific (24% from Isla del Coco) and only 18% from the Caribbean Sea. These results highlight the need to redirect research efforts on specific taxonomic groups and geographic regions (i.e., Caribbean). Based on our review, improving the quality and quantity of fisheries landing statistics, as well as determining the degree of overlap between chondrichthyans and Costa Rican fisheries remains a priority. We proposed an adaptive management framework for chondrichthyan fisheries in data-poor countries where management goals/targets are clearly defined. This framework could strengthen the conservation of chondrichthyan populations in Costa Rica and the region.
Keywords: Chimeras; Conservation approaches; Data-poor countries; Eastern Tropical Pacific; Management; Population declines; Rays; Sharks